The staff of Oedipus : transforming disability in ancient Greece - Rose, Martha L., 1957- (Corporealities., 2003)
"The Staff of Oedipus looks at a wide range of writing on disability within the framework of ancient social history. Martha L. Rose examines not only ancient literature, but also evidence from papyri, skeletal remains, inscriptions, sculpture, and painting, as well as modern sources, including disability autobiographies, medical research, and the burgeoning scholarship and theoretical work in the field of disability studies."--Jacket